AGRO-ECONOMIC EFFICIENCY OF DIFFERENT BASIC SOIL TILLAGE METHODS ON MAIZE AREAS - Taranenko, S.V.; Chaika, T. O.; Tiupka, Ya. M. (Scientific Progress & Innovations, 2019)
The actuality of using such basic soil tillage methods, which help to save natural soil fertility and ensure agro-economic efficiency of grain maize cultivation (on the example of Delphin hybrid) was given in the ar-ticle. The research tasks were to determine the following: the influence of different basic soil tillage methods (plowing, sub-surface cutting, and shallow tillage) on the elements of crop structure and yields of maize grain; economic efficiency of various basic soil tillage methods for grain maize. Plant sampling and pheno-logical observation of plants were performed according to the methodology developed by the Institute of Grain Management of NAASU. Indexes of maize crops structure were evaluated according to the methods of the State Commission of Crop Variety Testing named after Maisyrian. Crop yields were determined by cut-ting and converting to 100% purity and basic humidity. Indexes of maize grain quality were determined ac-cording to the methods of the current state standards. All experimental data were analyzed statistically using STATISTICA ver. 7.0 software. The analysis of the elements of maize crop structure shows considerable de-creasing the number of maize ears per 100 plants at plowing (up to 98 pcs. instead of 118 pcs.). The index of grain weight from 1 m2 was the highest in the variant with plowing – 982 g/m2 and the lowest – in the variant with shallow tillage – 697 g/m2. Yields of maize grain under plowing (942 kg/ha) were higher by 17 % as compared with the variant of using shallow tillage. Yields of maize grain in the variant of using sub-surface cutting were in the middle – 861 kg/ha. The conducted calculations of economic efficiency proved the expe-diency of plowing which leads to increasing maize productivity and profitability level by 19 % and 38 % as compared with other basic soil tillage methods.